2017
DOI: 10.1038/s41598-017-09843-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface defects on the mechanical properties of ZnO nanowires

Abstract: The elastic modulus of ZnO nanowires was measured using a resonance method based on laser Doppler effect and their fracture strains were determined via two-point bending with the aid of optical nanomanipulation. The elastic moduli of ZnO nanowires with diameters of 78 to 310 nm vary from 123 to 154 GPa, which are close to the bulk value of 140 GPa and independent of the diameters and surface defects. However, the fracture strains of the ZnO nanowires depend significantly on their diameters, increasing from 2.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 52 publications
3
19
0
1
Order By: Relevance
“…Adjacent surfaces of tip and NW, and substrate and NW were modelled as Herztian contact pairs. During FEM simulation, a vertical load was applied by the tip, with a magnitude corresponding to a maximum contact pressure of 10 GPa, equal to the fracture strength of the NW[29]. As expected, the normal compressive stress experienced at the NW-substrate interface reached a maximum of 70 MPa at the NW's midpoint, and fell abruptly below 1 MPa at distance of just 1 µm from the midpoint.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Adjacent surfaces of tip and NW, and substrate and NW were modelled as Herztian contact pairs. During FEM simulation, a vertical load was applied by the tip, with a magnitude corresponding to a maximum contact pressure of 10 GPa, equal to the fracture strength of the NW[29]. As expected, the normal compressive stress experienced at the NW-substrate interface reached a maximum of 70 MPa at the NW's midpoint, and fell abruptly below 1 MPa at distance of just 1 µm from the midpoint.…”
mentioning
confidence: 68%
“…According to the elastic beam theory, can be estimated by [19], where , , , and are the elastic modulus, area moment of inertia, half length, and deflection of the NW, respectively. For the ZnO NWs being tested, GPa and were used [29], while the diameter, , and length, of the NW were measured by SEM. The frictional shear stress, , i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thin ZnS layer enhances ZnO hardness and elastic modulus due to improving quality of ZnO surface. 38,39 The passivation process of ZnO remove surface defects and signicantly improved its mechanical properties, for example, elastic moduli in case of ZnO nanowires. 38 The previous optical studies of the ZnO/ZnS nanolms showed that suldation process removed ZnO surface defects.…”
mentioning
confidence: 99%
“…38,39 The passivation process of ZnO remove surface defects and signicantly improved its mechanical properties, for example, elastic moduli in case of ZnO nanowires. 38 The previous optical studies of the ZnO/ZnS nanolms showed that suldation process removed ZnO surface defects. 24 The cathodoluminescence (CL) intensity of the band-to-band emission for ZnO/ZnS nanolayer was one order of magnitude higher than that of ZnO.…”
mentioning
confidence: 99%